2023
DOI: 10.1007/s11897-023-00618-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of COVID-19-Induced Cardiac Damage from Patient, In Vitro and Animal Studies

Abstract: Purpose of Review Though patient studies have been important for understanding the disease, research done in animals and cell culture complement our knowledge from patient data and provide insight into the mechanism of the disease. Understanding how COVID causes damage to the heart is essential to understanding possible long-term consequences. Recent Findings COVID-19 is primarily a disease that attacks the lungs; however, it is known to have important con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 124 publications
(136 reference statements)
0
1
0
1
Order By: Relevance
“…7, б). Эти результаты согласуются с данными других исследований, в которых были обнаружены патологические изменения, вирусная РНК и инфекционный вирус в сердце сирийских хомячков, заражённых SARS-CoV-2 [25,26]. Эти данные имеют особое значение в контексте того факта, что COVID-19 увеличивает риск развития миокардита у людей [27,28], что, вероятно, связано с повышенной экспрессией рецептора ACE2 в миоцитах человека [29].…”
Section: Discussionunclassified
“…7, б). Эти результаты согласуются с данными других исследований, в которых были обнаружены патологические изменения, вирусная РНК и инфекционный вирус в сердце сирийских хомячков, заражённых SARS-CoV-2 [25,26]. Эти данные имеют особое значение в контексте того факта, что COVID-19 увеличивает риск развития миокардита у людей [27,28], что, вероятно, связано с повышенной экспрессией рецептора ACE2 в миоцитах человека [29].…”
Section: Discussionunclassified
“…Many authors have pointed to vascular-mediated myocardial damage in the acute period of infection with the development of hemorrhage, necrosis, and thrombosis, which will inevitably lead to the formation of foci of replacement fibrosis [ 32 , 33 , 34 , 35 , 36 , 37 ]. Moreover, in the postacute period of coronavirus infection in a part of patients, we can also see persisting damage in the myocardium, which can potentially lay the foundation for the formation of autoinflammatory diseases and promote progressive collagen deposition in the interstitium [ 38 ]. Also, impaired T-cell function has been observed in the background of coronavirus infection, thus potentially leading to overstimulation of myocardial myofibroblasts and contributing to the development of a profibrotic state [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… 29 Another proposed mechanism underlying myocardial damage is ischaemic injury. 30 Upon examination of 40 hearts, Pellegrini et al identified microthrombus formation predominantly in small vessels as the main pathological cause of myocyte necrosis, accounting for 78.6% of cases. 31 …”
Section: Histopathological Findings Of Covid-19-related Myocardial In...mentioning
confidence: 99%